Coletivo andorinha : um ano de existência, de resistência, de política, de arte, de educação - Souza, Samara Azevedo de (2017)
This research aims to identify the existence and practices of the Coletivo Andorinha, which begin with the narrative of political discussions, but expand beyond that. It discusses the concept of social sculpture of Joseph Beuys, who understands an art in broader horizons, and as the mechanism of a new social order. It also brings some reflections of Paulo Freire in education, understanding its as a critical tool, political and intervention in the world. Finally, it weaves about the approximations between the concepts used and the practices of the Coletivo Andorinha